ROLE OF BRAIN NATRIURETIC PEPTIDE IN THE DIAGNOSIS AND MONITORING OF IRON DEFICIENT CHRONIC HEART FAILURE PATIENTS - Kashif, Nadia; Masood, Mohammad Tariq; Ullah, Hidayat; Gul, Adnan; Awan, Zahid Aslam; Hafizullah, Mohammad; Ahmed, Jawad; Taj, Abid Sohail (Journal of Postgraduate Medical Institute, 2016)
Objectives: To determine the efficacy of intravenous iron administration in iron deficient chronic heart failure patients and to determine the role of brain natreuretic peptide (BNP) in the diagnosis and monitoring of chronic heart failure patients. Methodology: The current study was a prospective analytical study. A total of 96 patients with symptomatic chronic heart failure (CHF) were selected through convenient sampling method. These were divided in to several groups based upon findings of echocardiography, 06 minutes' walk test and serum BNP. It was found that 38 patients were iron deficient. Intravenous (I/V) iron sucrose was administered to iron deficient patients weekly for 6 weeks followed by reassessment; the compliance rate was 87%. Results: Patients managed with I/V therapy showed significant improvement in all the clinical and biochemical parameters used in the study. New York Heart Association class shift was seen in 76% of patients. Conclusions: iron deficient induced CHF is common in our population. Parenteral iron administration (iron sucrose) is an effective modality for managing such patients. Serial BNP levels can be used to monitor the response to IV iron.